Aerobic training attenuates nicotinic acethylcholine receptor changes in the diaphragm muscle during heart failure - Souza, Paula Aiello Tomé de [UNESP]; Souza, Rodrigo Wagner Alves de [UNESP]; Soares, Luana Campos [UNESP]; Piedade, Warlen Pereira [UNESP]; Campos, Dijon Henrique Salomão [UNESP]; Carvalho, Robson Francisco [UNESP]; Padovani, Carlos Roberto [UNESP]; Okoshi, Katashi [UNESP]; Cicogna, Antonio Carlos [UNESP]; Matheus, Selma Maria Michelin [UNESP]; Dal-Pai-Silva, Maeli [UNESP] (My University, 2014)
Introduction: Heart failure (HF) is a progressive myopathy, with clinical signs of fatigue and limb weakness that can damage the nerve-muscle interaction, altering synaptic transmission and nicotinic acetylcholine receptors (nAChR) in neuromuscular junctions (NMJs). The diaphragm is composed of a mixed proportion of muscle fibres, and during HF, this muscle becomes slower and can alter its function. As exercise training is an accepted practice to minimise abnormalities of skeletal muscle during HF, in this study, we evaluated the hypothesis that aerobic training attenuates alterations in the expression of nAChR subunits in NMJs diaphragm during heart failure. Objective: The aim of this study was to evaluate the distribution and expression of nAChR subunits in the diaphragm muscle fibres of rats subjected to an aerobic training programme during HF. Methods: Control (Sham), control training (ShamTR), aortic stenosis (AS) and aortic stenosis training (ASTR) groups were evaluated. The expression of nAChR subunits (γ, α1, ε, β1 and δ) was determined by qRT-PCR, and NMJs were analysed using confocal microscopy. Results: We observed increased expression of the γ, α1 and β1 subunits in the AS group compared with the ASTR group. The distribution of NMJs was modulated in these groups. Discussion: HF alters the mRNA expression of nAChR subunits and the structural characteristics of diaphragm NMJs. In addition, aerobic training did not alter NMJs morphology but attenuated the alterations in heart structure and function and in nAChR subunit mRNA expression. Our findings demonstrate the beneficial effects of aerobic exercise training in maintaining the integrity of the neuromuscular system in the diaphragm muscle during HF and may be critical for non-pharmacological therapy to improve the quality of life for patients with this syndrome.
Keywords: Skeletal muscle; Heart failure; Aerobic training; Neuromuscular junction; Nicotinic acetylcholine receptors